A The Perception PERSEPSI SISWA TERHADAP GOOGLE CLASSROOM SEBAGAI LMS PEMBELAJARAN MATEMATIKA SELAMA PANDEMI COVID-19 - I Wayan Somayasa (Wahana Matematika dan Sains: Jurnal Matematika, Sains, dan Pembelajarannya, 2022)
ABSTRACT The Covid-19 pandemic in Indonesia affects the educational aspect, the learning process shifts from conventional (face-to-face) learning in the classroom to online learning. One of the important elements of implementing online learning is the availability of LMS. Google Classroom is one of the LMS that can be used in the online learning process. This LMS is supported by various features that can be elaborated to support the learning process. In this study, students' perceptions were analyzed and interpreted on the use of Google Classroom in the learning process during the Covid-19 pandemic. Data was collected by providing research instruments in the form of a questionnaire consisting of 10 statements and equipped with 5 answer options to each student via google form. Analysis and interpretation showed that, 44.98% of students felt happy in the integrated learning process of google classroom in the learning process during the Covid-19 pandemic, 51.14% of students felt happy with the acquisition of grades during the process, google classroom assisted learning, 52.97% feel happy in doing independent assignments given through the LMS google classroom, 53.20% feel excited about the implementation of google classroom 52.05% students feel neutral (normal) about the tasks given by the teacher during the learning process assisted by google classroom, 36.30% students feel interested in implementing google classroom as an LMS in the learning process, 39.73% feel enthusiastic about the google classroom assisted learning process, 40.41% students think that the google classroom assisted learning process is normal, 20.32% students think that the teacher the implementation of google classroom in the learning process is in the easy category, and 41.78% of students understand how to implement google classroom in the learning process after being explained by the teacher. Keywords: Covid-19, Google Classroom, LMS